2012
DOI: 10.1016/j.ccr.2012.02.019
|View full text |Cite
|
Sign up to set email alerts
|

VHL-Regulated MiR-204 Suppresses Tumor Growth through Inhibition of LC3B-Mediated Autophagy in Renal Clear Cell Carcinoma

Abstract: Summary The von Hippel-Lindau tumor-suppressor gene (VHL) is lost in most clear cell renal cell carcinomas (ccRCC). Here, using human ccRCC specimens, VHL-deficient cells, and xenograft models, we show that miR-204 is a VHL-regulated tumor suppressor acting by inhibiting macroautophagy, with MAP1LC3B (LC3B) as a direct and functional target. Importantly, higher tumor grade of human ccRCC was correlated with a concomitant decrease in miR-204 and increase in LC3B levels, indicating that LC3B-mediated macroautoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
254
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(266 citation statements)
references
References 44 publications
11
254
1
Order By: Relevance
“…Thus, the role and mechanism of miR-7 in SBNETs merits further investigation, and it would also be important to evaluate ciRS-7 expression. Similarly, whilst we found upregulation of miR-204 in SBNETs, it has been seen as downregulated in gastric cancer (Sacconi et al 2012, colorectal cancer (Yin et al 2014) and clear cell renal cell carcinoma (Mikhaylova et al 2012). Thus, its increased expression and role in SBNETs remains unknown.…”
Section: Global Mirna Profiling Reveals a Signature Specific For Smalmentioning
confidence: 43%
“…Thus, the role and mechanism of miR-7 in SBNETs merits further investigation, and it would also be important to evaluate ciRS-7 expression. Similarly, whilst we found upregulation of miR-204 in SBNETs, it has been seen as downregulated in gastric cancer (Sacconi et al 2012, colorectal cancer (Yin et al 2014) and clear cell renal cell carcinoma (Mikhaylova et al 2012). Thus, its increased expression and role in SBNETs remains unknown.…”
Section: Global Mirna Profiling Reveals a Signature Specific For Smalmentioning
confidence: 43%
“…miRNAs are known to contribute to multiple tumorigenic steps in human cancers, including RCC. Recent studies have identified regulatory activities of miRNAs in ccRCC cell growth (4)(5)(6)(7)(8), apoptosis (5,6,8,9), migration, and invasion (5)(6)(7)(8). A predominant and systemic alteration in miRNA expression during renal carcinogenesis has been indicated by present studies of miRNA expression profiling (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 71%
“…In addition, downregulation of miR-204 has been documented in several types of cancers. [37][38][39][40][41] Decreased expression of miR-204 results in overexpression of its target, myeloid cell leukemia sequence 1 (Mcl-1) mRNA, and induces anti-apoptotic signaling in pancreatic cancers. 42 miR-204 also regulates expression of an oncogene, neurotrophic receptor tyrosine kinase B, and promotes metastasis in endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%